2021
DOI: 10.1038/s41598-021-90237-z
|View full text |Cite
|
Sign up to set email alerts
|

A machine-learning-based alloy design platform that enables both forward and inverse predictions for thermo-mechanically controlled processed (TMCP) steel alloys

Abstract: Predicting mechanical properties such as yield strength (YS) and ultimate tensile strength (UTS) is an intricate undertaking in practice, notwithstanding a plethora of well-established theoretical and empirical models. A data-driven approach should be a fundamental exercise when making YS/UTS predictions. For this study, we collected 16 descriptors (attributes) that implicate the compositional and processing information and the corresponding YS/UTS values for 5473 thermo-mechanically controlled processed (TMCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…They observed that the nonlinear algorithms outperformed the linear algorithms, with many of the algorithms producing acceptable results. 131 …”
Section: Applications Of Generative Models In Materials Sciencementioning
confidence: 99%
See 3 more Smart Citations
“…They observed that the nonlinear algorithms outperformed the linear algorithms, with many of the algorithms producing acceptable results. 131 …”
Section: Applications Of Generative Models In Materials Sciencementioning
confidence: 99%
“…This presents the perfect opportunity to use machine-learning techniques to speed up the structural materials discovery process. , Researchers have had some success in structural material property prediction using conventional machine-learning algorithms. For example, Lee et al were able to predict both the ultimate tensile strength and yield strength of over 5000 thermomechanically controlled processed steel alloys using 16 chemical descriptors. They employed 16 machine-learning algorithms including linear regression, RFs, SVMs, and gradient-boosted trees.…”
Section: Applications Of Generative Models In Materials Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…The system was tested using a blind validation procedure. The blind validation was highly successful showcasing the high potential and effectiveness of the new methodology in the eld of SMA foil-based applications [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%